PRODUCTION OF OGIRI (A LOCAL FERMENTED FOOD CONDIMENT FROM CASTOR OIL SEEDS) BY THE USE OF BACTERIAL STARTER CULTURE - Nweze, N. R; Ene, Christabel; Iheukwumere , Sam C; Ukwueze , N. M; Okoli , Chisom C. (Global Journal of Chemistry, Biology and Physics (GJCBP), 2023)
Fermented foods are products processed through the activities of microorganisms, where the weight of the microorganisms in the food is minimal. Ogiri is a paste derived from the local fermentation of castor oil seeds (Ricinus communis). It is a traditional food common among Easterners, serving as a condiment and flavoring material in various dishes. The substrate was obtained from vendors at New and Ogbete main markets located in Enugu North, Enugu State. It was promptly transferred to the Godfrey Okoye University Microbiological Laboratory, where it underwent anaerobic fermentation both in a laboratory setting and traditionally. The sample was diluted, pour-plated, sub-cultured, and colonies were counted. Bacillus sp yielded 150 viable colonies, while Lactobacillus and Micrococcus sp yielded 130 and 115 colonies, respectively. Pure cultures believed to be Bacillus sp, Lactobacillus sp, and Micrococcus sp, isolated from the traditional type using different media (Hi-crome bacillus agar, nutrient agar, and enrichment agar), were used to ferment fresh ogiri in the lab, and the results were evaluated. Bacillus sp produced the best results among the various strains. Temperature and pH variations of different ogiri samples (traditionally fermented ogiri, ogiri fermented with isolates, unfermented or fresh ogiri, and commercial ogiri) were determined and represented graphically. The proximate composition of these various ogiri samples was determined. The results, along with sensory evaluations, were subjected to ANOVA, which showed the significance level to be 95%.